2020
DOI: 10.1002/slct.201903492
|View full text |Cite
|
Sign up to set email alerts
|

Jatropha Oil Cake Based Activated Carbon for Symmetric Supercapacitor Application: A Comparative Study on Conventional and Hydrothermal Carbonization Processes

Abstract: Jatropha oilcake (JOC), a major agro industrial co-product was effectively converted into activated carbons employing KOH mediated chemical process for supercapacitor applications. The activated carbons were synthesized by employing conventional (CC) as well as hydrothermal carbonization (HTC) processes and investigated their impact on their physicochemical properties. The graphitization degree of the pristine and activated biocarbons was investigated through XRD and RAMAN analysis. BET surface area analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The synthesized composite showed high specific capacitance, porosity and conductivity and found to be a promising electrode material for use in supercapacitors. Furthermore, porous carbon [190], bamboo fibers [191], Jatropha oil cake-based activated carbon [192], birnessite-type MnO 2 /carbon [193], palm oil-based supercapacitor [194], Co/MnO/CoMn 2 O 4 @RHs [195], polythiophene (PTh) nanofibers [196], hierarchical porous carbons (HPCs) [126], and porous carbons derived from laminaria japonica [190] were used as electrode materials in supercapacitors, which were synthesized through carbonization technique. Figure 11 represents a schematic illustration of the synthesis of porous carbons derived from Laminaria japonica.…”
Section: Carbonization Methodsmentioning
confidence: 99%
“…The synthesized composite showed high specific capacitance, porosity and conductivity and found to be a promising electrode material for use in supercapacitors. Furthermore, porous carbon [190], bamboo fibers [191], Jatropha oil cake-based activated carbon [192], birnessite-type MnO 2 /carbon [193], palm oil-based supercapacitor [194], Co/MnO/CoMn 2 O 4 @RHs [195], polythiophene (PTh) nanofibers [196], hierarchical porous carbons (HPCs) [126], and porous carbons derived from laminaria japonica [190] were used as electrode materials in supercapacitors, which were synthesized through carbonization technique. Figure 11 represents a schematic illustration of the synthesis of porous carbons derived from Laminaria japonica.…”
Section: Carbonization Methodsmentioning
confidence: 99%
“…The activated carbon obtained through the thermal activation process showed the highest specific surface area of 904.72 m 2 g −1 . We have also reported the fabrication of activated carbon from jatropha oil cake utilizing conventional and hydrothermal carbonization processes through KOH enabling the chemical activation process 135. The specific surface areas of the activated biocarbon materials achieved at 800 °C by conventional and hydrothermal carbonization were found to be 678.1 and 746.7 m 2 g −1 , respectively.…”
Section: Oil Cake‐based Biocarbon Materialsmentioning
confidence: 98%
“…HTC processes are extensively applied for the conversion of different types of biomasses into carbon products; however, the conversion of oil cake residues into biocarbon materials has not been explored as much. Only the oil cakes of rapeseed 78, jatropha 135, Pongammia pinnata , and tung 99 were investigated for hydrothermal conversion into biocarbon materials. It was found that the activated biocarbon produced through HTC showed a higher specific surface area compared to the respective conventional carbonization process.…”
Section: Oil Cake‐based Biocarbon Materialsmentioning
confidence: 99%
See 2 more Smart Citations